Sistem Pendukung Keputusan Pemilihan Mahasiswa Berprestasi Menggunakan Metode Profile Matching di FMIPA Uncen - Mochammad Fachorrozi; S Supiyanto; Mingsep Rante Sampebua; Remuz MB Kmurawak (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The Faculty of Mathematics and Natural Sciences, University of Cenderawasih, regularly selects outstanding students every year. Currently, the process of selecting outstanding students is carried out conventionally which results in the emergence of several problems such as missing data, ineffective report management, and data vulnerability. Decision support systems (DSS) are computer systems that help manage data into information that can help make the right decisions. The profile matching method is a method in SPK that compares individual competitions to award competitions so that the differences in competition (also called gaps) can be identified. The Decision Support System for Selection of Outstanding Students Using the Profile Matching Method is made web-based so that it is more dynamic in interoperability and supports multiplatform ecosystems. This system is created using the PHP programming language with the Codeigniter framework, and MySQL database. Based on the test results, it was concluded that the system with these 4 actors (administrator, study program head, jury and students) could run well, using the black box testing system. The parameters used in analyzing the profile matching of outstanding students are GPA, Scientific Writing, English Language Proficiency, Other Skills, Student Semester and the organization joined. By adding the weighting, the appropriate profile matching is obtained.